Arctic Environmental Test of Direct Fire Cannon (Tank and Anti-Tank Weapons). - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1970)
The Environmental Test Procedure describes test methods and techniques for evaluating the performance and characteristics of direct fire cannon (tank and anti-tank weapons) under arctic winter environmental conditions. (Author)